Political Violence in Nigeria and Its Implication for National Development - Anweting, Kevin Ibok; Ogar, Ogar Anthony (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2018)
Political violence is a major impediment to Nigeria’s national development. With the restoration to democratic rule in May 1999, high expectations were raised that the new democratic dispensation would resolve the risk of Nigeria’s political violence, while speeding the country’s economic and social transformation. It’s worrying that since democratic rule returned, Nigeria has experienced a degree of unprecedented political violence that has crippled the efforts of national development. The fundamental thrust of this paper is to investigate the incidence of Nigeria’s political violence and assess its national development consequences. The paper shows that political violence dissuades domestic and foreign investment in our economy, triggers government loss of revenue and resources, and results in the election of unqualified representatives to the detriment of the country’s economic and social progress. This paper proposes reducing wages paid to political office holders, and politicians should strive to achieve national unity instead of growing religious and ethnic tensions. Lastly, National resources should also be equitably distributed by the government.